Indirect innovation management by platform ecosystem governance and positioning: Toward collective ambidexterity in the ecosystems - Inoue, Yuki (Technological forecasting & social change, 2021)
•Ecosystem governance and positioning can be utilized for innovation management.•Medium level of distinctive positioning leads success of innovation ambidexterity.•Larger openness can generate benefits at medium level of distinctive positioning. This study outlines the implications of ecosystem governance and positioning regarding the indirect control of complementors’ incremental and radical behaviors in goods development and successful innovations. The study tested how the degree of openness as an indicator of governance and the degree of distinctiveness as an indicator of the positioning influenced the direction and sales performance of complementary goods by employing 9,780 samples of Japanese video game software. The statistical results showed that an increase in both openness and distinctiveness facilitates radical-oriented behavior, while the sales of complementary goods rise as openness increases at the medium level of distinctiveness. Consequently, this study indicates that high openness and appropriate distinctiveness contribute to securing ambidexterity on the platform ecosystems to facilitate balanced software development and larger sales performance.